Dynamics of finite groups acting on the boundary of homogenous rooted tree - Szaszkowski, Z. (Algebra and Discrete Mathematics, 2003)
Criterion of embedding of finite groups into the automorphism groups of a homogenous rooted tree of a spherical index n is formulated. The sets of natural numbers which are the lengths of all orbits of finite groups acting on the boundary of tree are described.